2019
DOI: 10.5194/acp-19-10447-2019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and sources of aerosol aminiums over the eastern coast of China: insights from the integrated observations in a coastal city, adjacent island and surrounding marginal seas

Abstract: Abstract. An integrated observation of aerosol aminiums was conducted in a coastal city (Shanghai) in eastern China, a nearby island (Huaniao Island), and over the Yellow Sea and East China Sea (YECS). Triethylaminium (TEAH+) was abundant over Shanghai but not detected over the island and the open seas, suggesting its predominantly terrestrial origin. By contrast, relatively high concentrations of dimethylaminium (DMAH+) and trimethylaminium + diethylaminium (TMDEAH+) were measured over the ocean sites, indica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 78 publications
1
34
0
Order By: Relevance
“…The higher DEA‐containing particle counts in the East China Sea detected in this study are consistent with the results of previous studies. Zhou et al (2019) reported relatively high concentrations of DEA‐containing particles in the East China Sea compared to the adjacent city, indicating the significant contribution of marine sources to the DEA‐containing particle counts. As shown in Figure 1, higher DEA‐containing particle counts were observed in case 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The higher DEA‐containing particle counts in the East China Sea detected in this study are consistent with the results of previous studies. Zhou et al (2019) reported relatively high concentrations of DEA‐containing particles in the East China Sea compared to the adjacent city, indicating the significant contribution of marine sources to the DEA‐containing particle counts. As shown in Figure 1, higher DEA‐containing particle counts were observed in case 1.…”
Section: Resultsmentioning
confidence: 99%
“…MMA‐containing particles are the dominant amine‐containing particles in urban areas (Ho et al, 2015; Liu et al, 2017). High concentrations of TMA‐containing particles have also been detected in urban (Zhang et al, 2012) and marine areas (Zhou et al, 2019). DEA‐containing particles are the dominant amine‐containing particles in marine areas (Fierz‐Schmidhauser et al, 2010; Xie et al, 2018; Zhou et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations